INFLUENCE OF MACROCYCLIC COORDINATION COMPOUNDS OF COPPER (III) ON THE PRODUCTIVITY OF VIRUSINDICATED SPRING WHEAT PLANTS: DOI: https://doi.org/10.17721/1728-2209.2018.1(55).19 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
Viral plant diseases cause crop losses and deterioration in product quality. One of the most widespread and harmful for wheat is Wheat streak mosaic virus. In this work, effect of two cooper (III) macrocyclic coordination compounds on growth and development of spring wheat plants infected with Wheat streak mosaic virus is investigated. The macrocyclic complexes have been obtained by template synthesis by reaction of oxalyl dihydrazide with carbonyl compounds (cyclohexanone or formaldehyde in the presence of copper(II) salts and atmospheric oxygen in aqueous solution. Identity and purity of the isolated compounds was confirmed by elemental analysis and powder X-ray analysis. The structure of the complexes was established by means of single crystal X-ray analysis. Aqueous solutions of both complexes can exist indefinitely long at ambient conditions without any signs of destruction. It was found that compounds increased plant weight and its dry matter content depending on the application method. In two variants, the seeds were sprouted on distilled water and treated with 0.05% solution of the studied complexes and in two other variants the seeds were soaked in 0.1% solutions of the same complexes, and then sprouted at 22°С. A positive effect on non-specific plant resistance upon foliar treatment with sodium-containing compound has been detected. Seed soaking with solutions of complex compounds result in overall positive impact on wheat development. The lithium and potassium counter cation-containing compound increased the weight of the ground part and root system, while compound with sodium counter cation - dry matter content in the roots in both healthy and virus infected plants. This indicates about the stimulation of resistance processes in wheat plants to WSMV-infection.
Keywords: copper (ІІІ) coordination compounds; plant viruses; wheat striped mosaic virus; productivity